(untitled) (Revista Española de Fisiología, 1959)
The dephosphorylation and deamination of hypoxanthine and adenine nucleotides and nucleosides has been separatelystudied in preparations of bone marrow of the epiphyseal and metaphyseal spongiosa and of the diaphyseal channel. A stronger dephosphorylating activity is shown by the marrow of metaphyseal spongiosa, which has ATPase, ADPase, AMPase, ITPase, IDPase, IMPase, ADPdeaminase but lacks adenylate and adenosine deaminases. The marrows of epyphyseal spon giosa and from the diaphysis lack AMPase and show the other dephosphorylating activities at a lower degree, but actively deaminate all adenine nucleotides and the nucleoside. Glucose is aminated by either glutamine, adenosine or an adenine nucleo tide in presence of the same marrow preparations. It seems likely that the synthesis of glucosamine is not preceded by the phosphorylation of the hexose.